Dual oxidase 1 is dispensable during Mycobacterium tuberculosis infection in mice - Gupta, Tuhina; Sarr, Demba; Fantone, Kayla; Ashtiwi, Nuha Milad; Sakamoto, Kaori; Quinn, Frederick D.; Rada, Balázs (Frontiers in Immunology, 2023)
Mycobacterium tuberculosis (Mtb) is the primary cause of human tuberculosis (TB) and is currently the second most common cause of death due to a single infectious agent. The first line of defense against airborne pathogens, including Mtb, is the respiratory epithelium. One of the innate defenses used by respiratory epithelial cells to prevent microbial infection is an oxidative antimicrobial system consisting of the proteins, lactoperoxidase (LPO) and Dual oxidase 1 (Duox1), the thiocyanate anion (SCN-) and hydrogen peroxide (H2O2), which together lead to the generation of antimicrobial hypothiocyanite (OSCN-) in the airway lumen. OSCN- kills bacteria and viruses in vitro, but the role of this Duox1-based system in bacterial infections in vivo remains largely unknown. The goal of this study was to assess whether Duox1 contributes to the immune response against the unique respiratory pathogen, Mtb. Duox1-deficient (Duox1 KO) and wild-type (WT) mice were infected with Mtb aerosols and bacterial titers, lung pathology, cytokines and immune cell recruitment were assessed. Mtb titers in the lung, spleen and liver were not different 30 days after infection between WT and Duox1 KO mice. Duox1 did not affect lung histology assessed at days 0, 30, and 90 post-Mtb infection. Mtb-infected Duox1 KO animals exhibited enhanced production of certain cytokines and chemokines in the airway; however, this response was not associated with significantly higher numbers of macrophages or neutrophils in the lung. B cell numbers were lower, while apoptosis was higher in the pulmonary lesions of Mtb-infected Duox1 KO mice compared to infected WT animals. Taken together, these data demonstrate that while Duox1 could influence leukocyte recruitment to inflammatory cell aggregates, Duox1 is dispensable for the overall clinical course of Mtb lung infection in a mouse model.